Assessment of Top Ten NIRF 2020 Rank Universities Libraries: A Webometric Study - Verma, Umesh Kumar; Singh, Shiv (Journal of Data Science, Informetrics, and Citation Studies)
Websites serve as information gateways and play an important role in information dissemination. The aim of this study is to examine the library websites of the Top 10 Universities that have been ranked by the National Institutional Ranking Framework (NIRF) for the year 2020. This study investigates the efficiency of library websites using webometric indicators and examines the University's library websites based on various links, and ranks the websites on the basis of their internal and external web impact factors. The result visualized that the web impact factor of the library website of Jamia Millia Islamia is the highest followed by the library website of the Indian Institute of Science and the library website of Manipal Academy of Higher Education among the top 10 University library websites. The study's findings will assist webmasters and library professionals in overcoming the limits that users confront and improving their websites.
Keywords: Webometric; Websites; Libraries website; NIRF; Links; Web impact factor; etc. Impact Factor.